Using Acetaminophen's Toxicity Mechanism to Enhance Cisplatin Efficacy in Hepatocarcinoma and Hepatoblastoma Cell Lines - Neuwelt, Alexander J (Neoplasia Press Inc., 2009)
BACKGROUND/AIMS: Acetaminophen overdose causes hepatotoxicity mediated by toxic metabolites generated through the cytochrome P450 enzyme. The objective of this study was to investigate whether acetaminophen (AAP) can enhance cisplatin (CDDP) cytotoxicity against human hepatocarcinoma and hepatoblastoma cells in vitro and whether this effect can be prevented by N-acetylcysteine (NAC). METHODS: In vitro studies (glutathione [GSH] level, cell viability, and immunoblot assays) were performed using human hepatocarcinoma and hepatoblastoma cells cultured in AAP, CDDP, and the combination of both with or without delayed NAC administration. The pharmacology and toxicology of high-dose AAP in rats were also examined. RESULTS: Acetaminophen decreased GSH levels in liver cancer cells in a dose- and time-dependent manner. Acetaminophen combined with CDDP had enhanced cytotoxicity over CDDP alone. The cytotoxicity caused by AAP plus CDDP was decreased by NAC, with the effectiveness being time-dependent. The GSH level was lowered in the liver but not in the blood or the brain in rats treated with a high dose of AAP (1000 mg/kg). The expression of CYP2E1 protein, a key cytochrome P450 enzyme, varies among species but is not correlated to AAP sensitivity in liver cancer cells. CONCLUSIONS: Our results suggest that a chemotherapeutic regimen containing both AAP and CDDP with delayed NAC rescue has the potential to enhance chemotherapeutic efficacy while decreasing adverse effects. This would be a promising approach particularly for hepatoblastomas regardless of cellular CYP2E1 protein level but could also be beneficial in other malignancies.